Comprehensive Evaluation of Late Season Peach Varieties (Prunus persica L.): Fruit Nutritional Quality and Phytochemicals - Dasha Mihaylova; Aneta Popova; Ivelina Desseva; Ivan Manolov; Nadezhda Petkova; Radka Vrancheva; Alexander Peltekov; Anton Slavov; Argir Zhivondov (Molecules, 2021)
Peaches are one of the most preferred seasonal fruits, and a reliable source of nutrients. They possess biologically active substances that largely differ among varieties. Hence, revealing the potential of several late season peaches is of present interest. Three commonly consumed varieties (“Flat Queen”; “Evmolpiya”; “Morsiani 90”) were studied in terms of nutritive and phytochemical content, as well as antioxidant activity with the use of reliable spectrophotometric and High Performance Liquid Chromatographic (HPLC) methods. An analysis of the soil was also made. The phytochemical data were subjected to principal component analysis in order to evaluate their relationship. The “Morsiani 90” variety had the highest minerals concentration (2349.03 mg/kg fw), total carbohydrates (16.21 g/100 g fw), and α-tocopherol (395.75 µg/100 g fresh weight (fw)). Similar amounts of TDF (approx. 3 g/100 g fw) were reported for all three varieties. “Flat Queen’s” peel extract was the richest in monomeric anthocyanins (2279.33 µg cyanidin-3-glucoside (C3GE)/100 g fw). The “Morsiani 90” variety extracts had the highest antioxidant potential, defined by 2,2-diphenil-1-picrylhydrazyl (DPPH), ferric-reducing antioxidant power (FRAP) and cupric ion-reducing antioxidant capacity (CUPRAC) assays.